2018
DOI: 10.1063/1.5042727
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Hall mobility and suppressed backward scattering in layered semiconductor Bi2O2Se

Abstract: We report on an ultrahigh Hall mobility exceeding 40 000 cm2/V s and a very long traditional scattering time in a trivial layered semiconductor Bi2O2Se. Shubnikov-de Haas (SdH) oscillations were observed in both the unsaturated longitudinal linear magnetoresistance Rxx and the transverse Hall resistance Rxy. The amplitude ΔRxy of SdH oscillations was phase-shifted approximately 180° with respect to ΔRxx, indicating the strong suppression of electron backward scattering. This was further proved by the evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…Additionally, Bi 2 O 2 Se may be used as an optical switch for the exploitation of compact and high-performance midinfrared pulsed laser sources [56]. In Reference [57] was found a strong reduction in amplitude of the universal conductance fluctuations and showed that this result agrees with the assumed strong spin-orbit interaction in the Bi 2 O 2 Se nanoplate. The strong spin-orbit interaction in Bi 2 O 2 Se nanoplates has also been confirmed through magnetotransport measurements [55].…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, Bi 2 O 2 Se may be used as an optical switch for the exploitation of compact and high-performance midinfrared pulsed laser sources [56]. In Reference [57] was found a strong reduction in amplitude of the universal conductance fluctuations and showed that this result agrees with the assumed strong spin-orbit interaction in the Bi 2 O 2 Se nanoplate. The strong spin-orbit interaction in Bi 2 O 2 Se nanoplates has also been confirmed through magnetotransport measurements [55].…”
Section: Introductionmentioning
confidence: 89%
“…12 Recently, it was found that the low temperature (about 2 K) Hall mobility can reach more than 2.0 Â 10 4 cm 2 s À1 V À1 in Bi 2 O 2 Se thin lm [13][14][15] and 4.0 Â 10 4 cm 2 s À1 V À1 in Bi 2 O 2 Se single crystal. 16 Very recently, we have observed a superior Hall mobility of 2.2 Â 10 5 cm 2 s À1 V À1 at 2 K in a high quality Bi 2 O 2 Se single crystal. 17 The high mobility in Bi 2 O 2 Se is possibly due to the self-modulation doping, i.e.…”
Section: Introductionmentioning
confidence: 93%
“…[8][9][10][11] Second, Bi 2 O 2 Se has an ultrahigh electron mobility. [12][13][14][15][16][17] An earlier work in 2012 found that the room temperature Hall mobility of Bi 2 O 2 Se single crystal was on the order of 300 cm 2 s À1 V À1 . 12 Recently, it was found that the low temperature (about 2 K) Hall mobility can reach more than 2.0 Â 10 4 cm 2 s À1 V À1 in Bi 2 O 2 Se thin lm [13][14][15] and 4.0 Â 10 4 cm 2 s À1 V À1 in Bi 2 O 2 Se single crystal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations